Analysis of Factors Influencing Sharia Economics Students' Interest in Using Digital Wallets (Case Study of E-Wallet Fund Users at Muhammadiyah Mataram University) - Saputra, Dalingga; Agustina, Ahadiah; Fitri Hidayanti, Nur (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The increasing phenomenon of non-cash payments and digital transactions has encouraged the emergence of various e-wallet service providers who are competing to provide convenient, safe, and easy-to-use payment solutions to customers. Can these funds provide confidence and satisfaction to students interested in using Muhammadiyah University in Palembang to provide influence and benefits to students? The method used is quantitative with multiple linear regression analysis techniques using SPSS Ver.26 software with a total of 67 respondents. The results of the research state that Trust and Satisfaction have a positive and significant influence on interest in using the Dana digital wallet among Universitas Muhammadiyah Mataram students.